Associated factors of Nigerian Nurses' Emotion regulation, perceived stress, and coping mechanism during COVID-19 Pandamic: a cross-sectional study - Agbonselohbor, Blessing; Aslanoğlu, Aziz; Bilgiç, Nurcan; Alsharawneh, Anas; A Elshatarat, Rami; T Saleh, Zyad; T Almagharbeh, Wesam; Yousef Al-Akash, Hekmat; E Sobeh, Dena; M Eltayeb, Mudathir (African health sciences, 2025)
Background: Nursing, marked by its demanding nature, often exposes professionals to elevated stress levels and emotional hurdles. Recognizing the determinants shaping nurses’ stress, emotional regulation, and coping mechanisms is imperative for fostering their welfare and maintaining superior patient care standards.Objective: This study aimed to explore the correlation between socio-demographic and work-related factors and nurses’ perceived stress, emotional regulation, and coping mechanisms.Methods: A cross-sectional study encompassing 200 nurses in Nigeria was conducted. Participants completed questionnaires evaluating socio-demographic details, the Perceived Stress Scale (PSS), Emotion Regulation Questionnaire (ERQ), and Coping Mechanism Scale. Statistical analyses, comprising t-tests and ANOVA, were employed to scrutinize variable associations.Results: Participants exhibited a mean score of 27.1 (±3.7) (out of 40) on the PSS, indicating heightened stress levels. Notably, cognitive reappraisal scored 32.2 (±5.2) (out of 42) on the ERQ, while expressive suppression scored 23.4 (±3.8) (out of 28), with a total ERQ score averaging 55.5 (±9.8) (out of 70), indicating moderate emotion regulation. Furthermore, participants scored 78.1 (±10.7) (out of 112) on the Coping Mechanism Scale, suggesting frequent utilization of coping strategies. While gender, age, religion, and employment status showed no significant correlations with stress levels, factors such as educational attainment, number of children, years of experience, department worked in, job position, and work environment satisfaction displayed noteworthy relationships. Various socio-demographic and work-related factors, including the number of children, years of experience, department worked in, and job position, demonstrated significant relationships with nurses’ emotional experiences and coping strategies.Conclusion: The study underscores the intricate interplay between socio-demographic and work-related factors in shaping nurses’ stress, emotional regulation, and coping mechanisms. Interventions tailored to address these factors and cultivate supportive work environments are vital for safeguarding nurses’ well-being and upholding exceptional patient care standards. Keywords: COVID-19 pandamic; stress; emotional regulation; coping mechanisms; socio-demographic factors; work-related factors; Nigeria.